Molecular epidemiology and antimicrobial resistance of Clostridioides difficile in Germany, 2014-2019 - Ahmed Mohamed Mostafa Abdrabou; Zia Ul Habib Bajwa; Alexander Halfmann; Alexander Mellmann; Anna Nimmesgern; Lena Margardt; Markus Bischoff; Lutz von Müller; Barbara Gärtner; Fabian K. Berger (Elsevier, 2021)
Clostridioides difficile is a Gram positive spore-forming rod and mainly responsible for nosocomial diarrhea in developed nations. Molecular and antimicrobial surveillance is important for monitoring the strain composition including genotypes of high epidemiological importance such as ribotype 027 (RT027) and corresponding resistance patterns.1535 isolates obtained from samples sent between 2014 and 2019 to the German National Reference Center (NRC) for diagnostic reasons (NRC strain set), and 1143 isolates from a Tertiary Care University Center in Saarland, Germany (non-NRC strain set), were evaluated using antibiotic susceptibility testing and ribotyping.In the NRC strain set, RT027 overtook RT001, the main RT found in the preceding studies, and dominated with 36.2%, followed by RT001 (13.3%), and RT014 (8.5%). Of note, since 2016 a constant decrease of RT027 could be noticed. In the non-NRC strain set a large strain diversity was present with RT014 (18%) and RT001 (8.9%) being most prevalent. In NRC samples, resistance towards metronidazole, vancomycin, moxifloxacin, clarithromycin and rifampicin was 2.7%, 0%, 57.1%, 53.2% and 19.2%, respectively. Metronidazole resistance was almost exclusively found in RT027 isolates. Rifampicin resistance was also observed predominantly in isolates of RT027, constituting an almost four-fold increase, when compared to preceeding studies in this region.In conclusion these data demonstrate that RT027 is a driver for rifampicin and metronidazole resistance, underlining the importance of continuous surveillance efforts.